It’s should be 12.04 after you do all the math and add it up
Answer:
Z-7
6-7
-1
Step-by-step explanation:
we have to replace the value of Z and then subtract by seven.
_________________
√(-√2-(-√2))²+(√3-2√3)²= 3
Answer:
could you possibly zoom in
Step-by-step explanation:
To divide the expression we proceed as follows:
12x⁴y²÷3x³y⁵
=12x⁴y²/3x³y⁵
=(12÷3)×(x⁴÷x³)×(y²÷y⁵)
when you divide number with the same base, you subtract the numerators:
=4×(x⁴⁻³)×(y²⁻⁵)
simplifying this we get
=4xy⁻³
Answer: 4xy⁻³